(untitled) (Journal of Engineering, 2023)
This research takes up address the practical side by taking case studies for construction projects that include the various Iraqi governorates, as it includes conducting a field survey to identify the impact of parametric costs on construction projects and compare them with what was reached during the analysis and the extent of their validity and accuracy, as well as adopting the approach of personal interviews to know the reality of the state of construction projects. The results showed, after comparing field data and its measurement in construction projects for the sectors (public and private), the correlation between the expected and actual cost change was (97.8%), and this means that the data can be adopted in the research study of the integration of parametric costs in a predictive model for future study. Changes in the parametric costs of construction projects substantially impact their time, cost, and quality and are a major barrier to their execution, necessitating research, analysis, and the development of the most effective solutions. The study aims to identify the parametric cost accurately through iterative tests and continuous improvements by presenting literature describing the history and characteristics of the parametric cost methodologies and identifying each methodology’s limitations, strengths, and weaknesses to promote a better understanding of their best practices and use for managing project cost